The Cost Effectiveness of Immunoglobulin vs. Hematopoietic Stem Cell Transplantation for CIDP - Burt, Richard K.; Tappenden, Paul; Balabanov, Roumen; Han, Xiaoqiang; Quigley, Kathleen; Snowden, John A.; Sharrack, Basil (Frontiers in Neurology, 2021)
Background: Intravenous immunoglobulin (IVIG) is effective as standard first line therapy for chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), but some patients remain dependent on its long-term use. Recently, we have reported that autologous non-myeloablative hematopoietic stem cell transplantation (HSCT) is an effective second line therapy for CIDP. Objectives: To compare the cost of chronic IVIG vs. autologous HSCT (a one-time therapy), we collected data on patients with CIDP undergoing HSCT between 2017 and 2019. This was compared with published literature on the costs and efficacy defined by the Inflammatory Neuropathy Cause And Treatment (INCAT) disability score, Medical Research Council (MRC) sum score, hand grip strength, and SF-36 quality of life (QOL) for CIDP. Methods: Between 2017 and 2019, nineteen patients with chronic CIDP (mean disease treatment duration prior to HSCT of 6 years) underwent autologous HSCT with mean cost of 108,577 per patient (range 56,327–277,119, standard deviation 53,092). After HSCT, 80% of patients remain IVIG and immune treatment free for up to 5 years. In comparison, published cost of IVIG treatment in the USA for an average CIDP patient exceeds 136,000 per year. Despite remaining treatment free, HSCT demonstrated greater improvement in efficacy compared to immunoglobulins. Recommendations: Given the long-term treatment-free remission and better outcome measurements, autologous HSCT is more cost effective than long-term IVIG treatment in patients with chronic CIDP. However, costs will depend on patient selection, the HSCT regimen, and regional variations. Further analysis of the health economics, i.e., cost/outcome ratio, of HSCT as therapy for chronically IVIG dependent CIDP is warranted.